The role of radiotherapy in patients with resected ampullary carcinoma: findings based on the SEER database. Issue 11 (November 2019) - Zhao, Wen; Wang, Biyuan; Zhao, Andi; Tian, Qi; Zhang, Lingxiao; Wang, Le; Zhao, Xiaoai; Yang, Jin; Dong, Danfeng
Abstract: Background: The role of adjuvant radiotherapy for resected ampullary carcinoma (AC) remains controversial. The aim of this study was to assess the effect of adjuvant radiotherapy on survival in patients who underwent resection for AC. Methods: The Surveillance, Epidemiology and End Results (SEER) database was used to identify patients diagnosed with AC from 2004 to 2012. Kaplan-Meier survival curve and multivariable Cox proportional hazards analyses were conducted to determine the effect of adjuvant radiotherapy on overall survival (OS) and disease-specific survival (DSS). Propensity score matching (PSM) method was used to balance the differences of clinicopathological characteristics between groups. Results: A total of 1227 patients were included. Patients who received adjuvant radiotherapy were younger, had more advanced T stage and N stage tumors and were more likely to receive chemotherapy (p < 0.001). Adjuvant radiotherapy failed to improve either OS (p = 0.119) or DSS (p = 0.188) in PSM cohorts. In subgroup analysis, no subgroup benefited from adjuvant radiotherapy and in patients older than 70 years, radiotherapy was associated with a worse OS and DSS. Conclusion: Patients with resected AC do not benefit from adjuvant radiotherapy.